INFORMATION ACCESSIBILITY, UTILISATION AND SOCIO-ECONOMIC VARIABLES AS PREDICTORS OF QUALITY OF LIFE OF RURAL WOMEN IN EKITI STATE, NIGERIA (2011)
The quality of life of people in developing countries, including Nigeria, is often adjudged to be lower than the expected standard. This is worse with women living in the rural areas whose lives are characterised by inadequate access and use of basic amenities of life. The situation is compounded by the women's lack of access to valuable information and non-utilisation of available information which could help them meet the challenges of daily living. The rural environment and the attendant socio-economic milieu pose additional limitation to the women's quality of life. Studies relating informational factors to quality of life of rural women appear to be rare in the field of library science. This study, therefore, investigated the extent to which information accessibility, utilisation and socio-economic variables (age, education, occupation, marital status, number of children, household size, type of house, rural dwelling status, employment status, income, average spending on food and standard of living), could predict the quality of life of rural women in Ekiti State, Nigeria. The study adopted the descriptive research design of the ex-post facto type. Multi stage sampling procedure was used to select 5000 rural women from 10 local government areas in Ekiti State. Three instruments were used: Information Accessibility Scale (r=0.87), Information Utilisation Scale (r=0.82) and Quality of Life Scale (r=0.84). Focus Group Discussions and interviews were also employed to complement the quantitative data collected. Six research questions were answered and four hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson Product Moment Correlation and Multiple Regression. Socio-economic variables, information accessibility and information utilisation had significant multiple correlation with quality of life (R=.69;p<0.05). These taken together, significantly predicted quality of life of rural women in Ekiti State (F=325.17, df=14;4985, p<0.05). The variables contributed 47.7% of the total variance in quality of life of rural women. Out of these, seven individually predicted the women's quality of life and these were information utilisation (?=.33), information accessibility (?=.32) type of house (?=.12) and marital status (? =.04), standard of living (? = .034), occupation (?=.03) and household size (?=.021). Information accessibility, information utilisation and socio-economic factors played significant roles in the quality of life of rural women. Therefore, government should provide special information centres to provide timely information that could improve the quality of life of rural women in Ekiti State.